Cost of Remediation of Nitrogen-Contaminated Soils Under CAFO Impoundments - C. Volland; J. Zupancic; J. Chappelle (Journal of Hazardous Substance Research, 2003)
Wastewater in manure storage basins or anaerobic treatment lagoons at confined animal feeding operations (CAFOs) may contain high levels of nitrogen, primarily in the ammoniacal form. Kansas law allows seepage from such impoundments at a rate of 1/8 to 1/4 inch per day (3.2 to 6.4 mm/d). Kansas State University researchers have recently characterized an ammonia plume at a depth of 10 feet or more under several CAFO lagoons and have modeled the potential for deeper penetrations in sandy subsoils. If the plume is not removed or contained after wastewater is removed from the impoundment, then exposure to oxygen from air or dissolved in precipitation will drive the transformation of ammonium to nitrate, which is mobile in the vadose zone. Based on a cleanup standard of 25 mg/kg of NH4-N, the total cost to remove or contain the nitrogen beneath federally permitted swine and dairy wastewater management basins now in operation in Kansas would be about $56 million. In most cases, the preferred remedial option would be the excavation and spreading of the contaminated material on farmland. However, deep plumes in sandy soils and limited access to farmland may dictate use of the backfill-and-cover option. The remedial cost for some operations not currently required to provide financial assurance for closure is estimated to range from $500,000 to $650,000.
Keywords: lagoons; liners; ammonia; closure; costs